Menelaah Arah Politik Hukum dan Nilai-Nilai Pancasila dalam Reformulasi Undang-Undang Konservasi Sumber Daya Alam Hayati - M. Yusuf Wirawan (Faculty of Law, Udayana University, 2025)
Law No. 32 of 2024 on Amendments to Law No. 5 of 1990 concerning the Conservation of Natural Resources and Ecosystems (Amended Conservation Law) is an important step in the effort to preserve Indonesia's natural resources and ecosystems, which face various issues such as deforestation and biodiversity loss. This paper analyzes the consistency of the Amended Conservation Law with the fundamental values of the Indonesian state and its legal policy direction using a normative juridical approach, specifically through statute approach and philosophical approach. The analysis reveals that the Amended Conservation Law demonstrates strong consistency with the core values of the Indonesian state, particularly Pancasila and the 1945 Constitution, by emphasizing the sustainable management of natural resources and social justice. The legal policy direction of this law aims to achieve societal welfare, environmental protection, and sustainable development, in line with the aspirations of the Indonesian nation.